All‐Printed Flexible and Stretchable Electronics. Issue 19 (1st March 2017) - Mohammed, Mohammed G.; Kramer, Rebecca
Abstract : A fully automated additive manufacturing process that produces all‐printed flexible and stretchable electronics is demonstrated. The printing process combines soft silicone elastomer printing and liquid metal processing on a single high‐precision 3D stage. The platform is capable of fabricating extremely complex conductive circuits, strain and pressure sensors, stretchable wires, and wearable circuits with high yield and repeatability.